2013
DOI: 10.1038/nature12801
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative production of a maximally entangled steady state of two quantum bits

Abstract: Entangled states are a key resource in fundamental quantum physics, quantum cryptography, and quantum computation [1]. To date, controlled unitary interactions applied to a quantum system, so-called "quantum gates", have been the most widely used method to deterministically create entanglement [2]. These processes require high-fidelity state preparation as well as minimizing the decoherence that inevitably arises from coupling between the system and the environment and imperfect control of the system parameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
390
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(398 citation statements)
references
References 43 publications
3
390
1
Order By: Relevance
“…Jt, 33.80.Gj, 34.50.Lf, Crystals of laser-cooled atomic ions form the basis of many experimental realizations of quantum logic gates [1][2][3] and simulations of quantum many-body physics [4][5][6]. In room-temperature vacuum systems, collisions with neutral background gas molecules limit quantum coherences and quantum logic operations [7].…”
mentioning
confidence: 99%
“…Jt, 33.80.Gj, 34.50.Lf, Crystals of laser-cooled atomic ions form the basis of many experimental realizations of quantum logic gates [1][2][3] and simulations of quantum many-body physics [4][5][6]. In room-temperature vacuum systems, collisions with neutral background gas molecules limit quantum coherences and quantum logic operations [7].…”
mentioning
confidence: 99%
“…Preparation of the maximum entangled state is still a central topic of interest. It has been shown that stationary quantum entanglement can be dissipatively prepared by engineering the bath enviroment [38][39][40][41]. By squeezing the enviroment, quantum entanglement between emitters can be also created [42][43][44].…”
Section: Quantum Entanglementmentioning
confidence: 99%
“…If suitably tamed and engineered, it can be used to perform several quantum information-processing tasks, including state preparation [2][3][4], universal quantum computation [1], quantum simulation [5,6], quantum memories [7][8][9], and quantum control [10]. Although at this point experiments are only at the level of proof-of-principle operations, this new framework provides novel motivation for the revival and further development of continuous-time quantum error correction (CTQEC).…”
Section: Introductionmentioning
confidence: 99%